The impact of financial and social performance of microfinance institutions on lending interest rate: A cross-country evidence - Afsheen Abrar (Cogent Business & Management, 2019)
The present paper examines the impact of financial and social performance of microfinance institutions (MFIs) on lending interest rate. The paper has covered five-star-rated MFIs in all the six regions of the world individually and collectively for the period of 2006-2012. Data for 382 MFIs belonging to 70 countries around the world have been taken from the Microfinance Information Exchange (Mix Market). Financial performance is captured through return on assets, return on equity, and operational self-sufficiency, whereas social performance is measured through average loan size and number of credit clients. The lending interest rate is a weighted average of the interest rates actually received by the MFIs from their clients. The paper incorporated some control variables to capture variations in size, age, location, and infrastructure of MFIs. Panel data estimation techniques have been applied to find out the empirical association between the selected variables. Most of the results have shown that cost of funding, return on assets (ROA), and the number of credit clients have a significant positive impact on lending interest rate around the world. However, depth outreach as depicted by average loan size has significant inverse relation with lending interest rates. Moreover, results also highlight different factors that affect the productivity of MFIs around the world.
Keywords: 650; lending interest rate; microfinance institutions; financial performance; outreach